Original paperA novel intracavitary applicator design for the treatment of deep vaginal fornices: preliminary dose metrics and geometric analysis - Damato, Antonio L.; Cormack, Robert A.; Viswanathan, Akila N. (Journal of Contemporary Brachytherapy, 2015)
Purpose: To investigate the dose distributions associated with a novel balloon sleeve placed over a standard cylinder applicator. Material and methods : A computed tomography (CT) scan of a sleeve balloon shaped to inflate into the vaginal fornices was used to digitize 1-, 3-, and 5-catheter configurations. Point doses for rectum, apex, and fornix were calculated and compared to the values associated with a standard cylinder plan not targeting the vaginal fornices. Inflation of the sleeve balloon in the vaginal fornices and dose coverage with constraints to the rectum, bladder, and sigmoid D2cc were evaluated. Results: Rectum, apex, and fornix doses were respectively 76%, 119%, and 44% for a standard cylinder; 190%, 310%, and 93% for a 1-catheter configuration; 98%, 109%, and 109% for a 3-catheter configuration; and 91%, 107%, and 96% for the 5-catheter configuration. In a patient analysis, expansion of the sleeve balloon into the vaginal fornices was confirmed. The 5-catheter configurations were associated with best coverage of the fornices and acceptable doses to rectum, bladder, and sigmoid. Conclusions : A 1-catheter configuration cannot be used clinically due to high rectal and apex dose. In theoretical analysis, the 3- and 5-catheter configurations showed > 96% coverage to the vaginal fornices with a clinically acceptable rectal dose. In a treatment simulation in a patient, a 5-catheter configuration showed 90% coverage of the fornices with acceptable doses to the organs at risk. The treatment of deep vaginal fornices results in an increased rectal dose compared to a standard cylinder plan.